IDEOLOGI KONSERVATISME DALAM PENDIDIKAN SENI MUSIK - Raafinsha Rahmaniar; Mardi Mardi (Sekolah Tinggi Theologia Abdiel, 2019)
The entry of various new cultures in the modern era led to the depletion of love for traditional cultures that were considered ancient. The purpose of this paper is to overcome the problems of society in the modern era which began to leave traditional values. The modern era which is marked by industrialization also fills the form of education. A form of education that prioritizes technical-practical abilities so as to sacrifice ethical-humanistic values. This form of education results in the reduction of human values. An education is needed that can foster students' awareness to love, respect, and appreciate existing cultural heritage so that it is not lost because it has been eroded by modernization. Arts education with conservatism ideology is the answer to that problem. In practice, art learning is carried out in appreciation and artistic creations on traditional values, which aim to preserve and preserve existing culture, so that the culture remains intact even in the midst of the swift currents of modernization.